Terminalia catappa L. (Combretaceae): Estudo da arte, caracterização farmacobotânica, prospecção fitoquímica e avaliação do efeito larvicida das folhas frente Aedes aegypti - DIAS, Cleverson Danrley Cruz (2023)
Terminalia catappa L. is a plant belonging to the family Combretaceae, with a wide use in Indian Indian, African and Asian medicine, and frequent distribution in tropical and subtropical countries, such as Brazil. Its leaves are generally used in the production of beverages, such as tea, and are also popular medicine as an antipyretic and antidiarrheal. Several researches are being conducted on the biological activities of Terminalia catappa L., having already been proven the antioxidant, anti-inflammatory, antitumor, antiviral and antidiabetic. These activities are attributed, basically, to the existence of phenolic compounds, of which some compounds have already been isolated and characterized. Thus, this work aimed to perform the study of the plant art, the pharmacobotanical characterization, chemical and biological prospection with focus on the larvicidal action of the red and green leaves of Terminalia catappa L. against Aedes aegypti. The study of the art of this species was performed through a survey of scientific studies on the chemical composition and chemical composition and biological properties of Terminalia catappa L. To this end, an integrated review of the literature literature by searching databases in the period 2015 to 2022 and selected articles with full text available, which presented analysis of the chemical components, biological activities biological activities related to extracts of Terminalia catappa L., as well as which part of the plant was used in the research. The main results indicated that the leaves of the plant are the most used part in the among the main biological activities studied, the antibacterial effect was found, as well as the phytochemical with regard to the phytochemical characteristics of the species, it was possible to notice that there is a variation of secondary metabolites. For the experimental study, the green and red leaves of Terminalia catappa L. were collected in the city of São Luís-MA and its exsicata is deposited in the Maranhão Herbarium of the Federal University of Maranhão. The leaves were morphoanatomical characterization study to determine identification parameters. For the chemical and biological studies, they were separately desiccated at room temperature and in the shade shade and then fragmented to a coarse powder. The powders were then subjected to maceration for 10 days, with daily stirring, using 70% ethanol as solvent and 1:10 hydromodule 1:10, obtaining hydroethanolic extracts. Tests to determine the phytochemical phytochemical profile were performed on the extracts. For the evaluation of cytotoxicity, the extracts were submitted to test with Artemia salina. To evaluate the larvicidal activity against A. aegypti, we followed the methodology proposed by WHO (2005). The green and red leaves present similar macroscopic similar macroscopic characteristics, differentiated by color, apex and size. Microscopically, no difference difference was observed between the leaves, being hypoestomatic, dorsiventral mesophyll type, presence of tector trichomes on the of tectors trichomes on the abaxial surface, biconvex central vein with main vascular bundle of amphiphloid symphyletic aspect. amphiphloic symphyletic aspect, with ducts in the inner phloem, sclerenchymatic fiber sheath next to the outer phloem and numerous drusen in the cortical parenchyma and pith. The phytochemical screening tests showed a similar profile between green and red leaf extracts, with simple phenols presence of simple phenols, flavonoids, tannins, saponins and differentiated only by the presence of steroids in green leaves and triterpenes in red leaves. The bioassay with Artemia salina showed greater safety of the green leaf extracts with LC50 higher than 550 μg/mL. In the test against larvae of A. aegypti, CL50 were obtained in the three mortality readings 24, 48 and 96h after the test, where showed better results for the green leaf extract CL50 ranging from 616.8 μg/mL in 24h to 535.3 μg/mL in 96h, compared to the red leaves extract CL50 ranging from 5,505.3 μg/mL in 24h to 1,899.5 μg/mL in 96h. These results demonstrated potential for use of products from green leaves of Terminalia catappa L. for control of A. aegypti larvae with possible safety determined by the in vitro toxicity assay performed. Considering that the green leaves leaves are the most numerous in the plant, these results also demonstrate the possibility of commercial commercial exploitation without risk to the species and because these leaves are the most used in medicinal practice, the determination of low toxicity is of great importance and also shows safety for use in areas of occurrence of these larvae with other non-target organisms. Finally, it is intended to contribute with the scientific research of plant species of our flora with possible safe and effective use in arbovirus control programs.